2017
DOI: 10.1016/j.ydbio.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Vegf signaling promotes vascular endothelial differentiation by modulating etv2 expression

Abstract: Vasculogenesis involves the differentiation of vascular endothelial progenitors de novo from undifferentiated mesoderm, their migration and coalescence to form the major embryonic vessels and the acquisition of arterial or venous identity. Vascular Endothelial Growth Factor (Vegf) signaling plays multiple roles during vascular development. However, its function during embryonic vasculogenesis has been controversial. Previous studies have implicated Vegf signaling in either regulating arteriovenous specificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 60 publications
3
25
0
Order By: Relevance
“…A recent study that used single-cell RNA analysis revealed that after S1-S2, non-EC populations (including cardiomyocytes and vascular smooth muscle cells) were in fact predominant among the differentiated cells, and less than 10% were actually identified as bona fide ECs ( 3 ). Studies have also shown that EC specification is dictated by a transient activation of ETV2 , which, in turn, depends on VEGF signaling ( 21 , 30 ). However, our study has revealed that the activation of endogenous ETV2 during S2 is inherently inefficient and that increasing the concentration of VEGF can only improve this constraint to a certain degree.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study that used single-cell RNA analysis revealed that after S1-S2, non-EC populations (including cardiomyocytes and vascular smooth muscle cells) were in fact predominant among the differentiated cells, and less than 10% were actually identified as bona fide ECs ( 3 ). Studies have also shown that EC specification is dictated by a transient activation of ETV2 , which, in turn, depends on VEGF signaling ( 21 , 30 ). However, our study has revealed that the activation of endogenous ETV2 during S2 is inherently inefficient and that increasing the concentration of VEGF can only improve this constraint to a certain degree.…”
Section: Discussionmentioning
confidence: 99%
“…We reported earlier that COX2/PGE2 induced VEGF-C/D production and tumor associated angiogenesis and lymphangiogenesis was inhibited by blocking EP4/PI3K/Akt signaling in breast cancer models (Xin et al, 2012; Majumder et al, 2014, 2018; Nandi et al, 2017). In zebrafish, the increase in vegfa/kdrl interactions upregulates the vascular transcription gene etv2 via Map-k signaling (Chetty et al, 2017), which in turn modulates the differentiation of arterial and venous expansions in a NOTCH-dependent manner. Overexpression of vegfa can repress the venous expansion possibly through the delta-NOTCH pathway, which is independent of etv2 (Chetty et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of VEGF stimulate arterial differentiation while lower levels are involved in the formation of venous vessels. Moreover, a strong reduction in VEGF signalling by blocking the VEGF receptor results in EC death and the arrest of vessel growth (Casie Chetty et al., ). In the retina, the primary hyaloid vasculature is replaced by the definitive one following a physiological hypoxic gradient generated by the increase in metabolic activity.…”
Section: Trophic Factorsmentioning
confidence: 99%